ANALISIS EFEKTIVITAS PENGELOLAAN KAS DI TOKO IRSA SANGALLA KABUPATEN TANA TORAJA - Dewi Pasongli; La Ode Turi; Sasmita Nabilah Syahrir (Komunitas Manajemen Kompetitif, 2026)
This research aims to determine the extent to which cash management is effectively implemented at Irsa Store S angalla, Tana Toraja Regency, as well as to identify the factors influencing its implementation. Effective cash management is a crucial factor in supporting the smooth operation and sustainability of businesses, especially for small enterprises with high transaction volumes.The research employed a qualitative method with a descriptive approach. Data collection techniques included interviews, observations, and documentation studies of financial records and transaction evidence from the store. The data obtained were analyzed based on the elements of cash management effectiveness according to Romney & Steinbart, which include cash planning, cash recording, and cash control.The results showed that the effectiveness of cash management at Irsa Store Sangalla is still not optimal. Cash planning is not conducted in a structured manner, cash recording has shortcomings in accuracy and completeness, and cash control is weak due to the lack of segregation of duties and non-standardized procedures. Nevertheless, the store has implemented several good practices, such as using digital systems for transactions and conducting regular cash reconciliations, enabling the business to maintain operational continuity and meet daily funding requirements.